The Influence Of Savings Motivation And Peers On Financial Habits Among Adolescents In Tolada Village - Rusni Rusanda; Hapid; Halim Usman (LP2M IAIN Palopo, 2026)
In the digital era, adolescents are increasingly exposed to a consumer lifestyle that can influence their financial habits. This study aims to analyze the influence of savings motivation and peer influence on the financial habits of adolescents in Tolada Village. This study used a quantitative approach with a correlational and cross-sectional design. A sample of 133 adolescent respondents aged 15–21 years was obtained through stratified random sampling. The data collection instrument was a questionnaire whose validity and reliability have been tested. Data analysis was performed using multiple linear regression using SPSS version 22. The results showed that simultaneously, savings motivation and peer influence significantly influenced adolescents' financial habits (p < 0.05). However, partially, neither savings motivation nor peer influence showed a significant influence individually. This finding indicates that adolescents' financial habits are more influenced by a combination of several factors simultaneously. Therefore, a holistic approach involving financial education, social support, and the role of the environment is key to forming healthy financial habits among adolescents